Functional Dimension Reveal Impacts of Non‐Native Fishes on Native Fishes and Ecosystem Functionality - Zhice Liang; Donald A. Jackson; Jiashou Liu; Chuanbo Guo (Global Change Biology, 2025)
Anthropogenic‐mediated invasions of non‐native species are leading to biodiversity loss in many trophic groups, with specific impacts on a wide range of ecosystem functions and services. However, the impacts of non‐native species on native species and ecosystem multifunctionality are not well understood, particularly due to the lack of long‐term studies that focus on the analysis of functional and phylogenetic diversities. Using a comprehensive dataset spanning nearly 80 years from Lake Erhai, China, we assessed the impact of non‐native fishes on the multidimensional diversity of native fishes, as well as the cascading effects on the multifunctional components of the ecosystem, including productivity, decomposition, and average multifunctionality. Over time, the multidimensional diversity of non‐native fishes steadily increased, whereas that of native species declined markedly. Concurrently, both ecosystem productivity and average multifunctionality exhibited significant upward trends. Long‐term invasion by non‐native fishes was significantly negatively correlated with the multidimensional diversity of native fishes. A consistent convergence–divergence–convergence pattern was observed in trait spaces and in functional and phylogenetic community patterns of overall fish communities. Ecosystem multifunctionality increased with non‐native fish functional diversity, though this positive relationship became negative at higher diversity levels. In contrast, native fish functional diversity and environmental factors—including average water level, Secchi depth, and annual precipitation—were consistently negatively associated with multifunctionality. These findings underscore the importance of integrating a functional perspective in biodiversity monitoring and management to enhance our understanding of, and foster more effective strategies for addressing, the long‐term impacts of non‐native species on native species and ecosystem multifunctionality.